Decision Making for Enhanced Health Security Managing Emerging Health Threats, Making Reasoned Choices, and Allocating Scarce Resources - Montibeller, Gilberto (Cham : Springer International Publishing : Imprint: Springer, 2022)
Health threats pose significant dangers to humankind and form a major source of human suffering and sorrow. Responsible leadership and reasoned decision making can significantly improve the arenas that are affected by health threats, through establishing a better allocation of very scarce resources for building health capabilities and for increasing health preparedness, responsiveness and resilience. This book examines how public health leaders can use the cutting-edge research from Decision Sciences to better manage emerging and re-emerging health threats, with a focus on enhancing health security. While these decisions must be informed by the best available evidence, they must also address competing priorities and key uncertainties and must mitigate critical risks, albeit in a cost-effective manner which seeks to maximize societal value. This is a book about how decisions on health security can be improved, both in terms of the content that is utilized in a health decision analysis and the decision processes that are employed in reaching a decision. This decision-focused perspective can help public health leaders and public health experts to increase the health preparedness of health systems, the task of which involves improving health capabilities, increasing the robustness of health systems against health threats, as well as strengthening health resilience and the responsiveness of these systems against disease outbreaks.
Making Health Security Decisions: Challenges and Complexities -- Making Reasoned Health Security Decisions: Key Concepts and Main Benefits -- Framing Health Security Decisions -- Specifying Relevant Objectives and Consequences in Health Security Decisions -- Assessing Impacts of Threats and Health Security Actions -- Defining Risk Limits, Trade-Offs, and Marginal Value in Health Security Decisions -- Developing Decision Alternatives for Enhanced Health Security -- Evaluating Health Threats and Health Security Actions with Multiple Consequences -- Evaluating Health Threats and Health Security Actions under Uncertainty -- Selecting the Best Options for Enhanced Health Security -- Deciding and Implementing Health Security Actions and Promoting Systematic Learning.
Keywords: Operations research; Health services administration; Medical policy; Public health; Operations Research and Decision Theory; Health Care Management; Health Policy; Public Health